Macrophage in periodontal inflammation - Kuzenko, Yevhen; Romanyuk, Anatoly; Politun, Antonina (Journal of Stomatology, 2017)
Aim of the study. To investigate the expression of CD68 and HSP90AA1 in periodontal inflammation. Methods. A total of twenty-seven patients (giant-cell epulis) and thirty patients (acute and chronic inflammations) have been examined for expression of CD68 and HSP90AA1 by hematoxylin – eosin and immunohistochemistry. Results. Strong giant-cell positivity for CD68 was observed in 100% of patients whereas only 85.31% of giant-cell was positive for HSP90AA1 (p<0.05). Strong macrophage immunoreactivity for CD68 was figured in acute 23.2±1.3%, and in chronic 83.1±5.6% (p<0.05) inflammation. Immunoreactivity for HSP90AA1 was fixed in acute and chronic inflammation 98.2±1.79%. Conclusion. Inflammatory macrophages are a group of cells with protective functions, macrophages being more set up in chronic inflammation. Central giant cell epulis is the multinucleated macrophages, formed as a result of chronic inflammation. Population of macrophages resulted in bone resorption.